Colonialism as Reflected in Forster’s A Passage to India - Tini Mogea (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
This research is intended to reveal colonialism in Forster’s A Passage to India. This is a qualitative research project since the data are in the form of words rather than numbers. The data were taken from the work itself and other relevant books supporting the analysis. In analyzing the data, the writer used a mimetic approach. The results show that the British colonize Indians by controlling them politically, that is, by gaining positions of power and authority. It is clearly seen that every important governmental position in India is occupied by British people. It is also undeniable that every public policy made is only for the benefit of the British government in India. It causes many effects to the colony and even the colonists. For the colony people, colonialism forms for them an antipathy toward the entire membership of the colonists and becomes a factor for them to stand together and legitimize themselves as a nation that is separated from and appreciated by other nations. On the other side, the colonists always think that they have a higher position than the colony people. Since the colonists have better technological development, they consider that they are superior to them and deserve to colonize them. Their superiority mindset has led them to harbor racial prejudice toward the colony people. The colonists think that the colony people have a negative attitude just because they are the colony.